Varietal Screening of Rice Genotypes for the Rice Weevil, Sitophilus oryzae (Linnaeus) (Curculionidae: Coleoptera) at Laboratory Condition - Pal, M.K.; Tiwari, S.; Regmi, R.; Ali, F. Md. (Journal of Agriculture and Environment, 2021)
The rice weevil, Sitophilus oryzae (Linnaeus) is a major pest of rice at storage condition in Nepal. A lab experiment was conducted for varietal screening of rice genotypes against S. oryzae at the National Rice Research Program, Hardinath, Dhanusha, Nepal in 2020. The study was carried out in Completely Randomized Design (CRD) in a three replicates. Fifty gram of each seven popular rice genotypes i.e Sambha Mansuli Sub-1, Ramdhan, Radha-11, Bahuguni-1, Bahuguni-2, Hardinath-2 and Lalka Basmati were used to screen the potential weevil resistant rice cultivars. Ten pairs of newly emerged adult S. oryzae of uniform age obtained from stock culture were released in each plastic jar in no-choice tests, while twenty five pairs of S. oryzae were released in the center, in choice tests. Results were evaluated based on the grain damage percent, weight loss percent, and total live weevil population for 90 days from the date of experiment. The result demonstrated that Lalka Basmati was the least damaged rice cultivar followed by Bahuguni-2. The highest weevil population over 90 days was recorded in Sambha Mansuli Sub-1 followed by Hardinath-2 and the least weevil population was found on Lalka Basmati followed by Bahuguni -2 in both test conditions. Lowest to highest damage ranking of rice genotypes was: Lalka Basmati<Bahuguni-2<Bahuguni-1<Radha-11<Ramdhan<Hardinath-2<Sambha Mansuli Sub-1. Thus, promotion of Lalka Basmati & Bahuguni-2 varieties is recommended to reduce the infestation of rice weevil in the storehouse condition. This information is useful for host plant resistant breeding program for the plant breeder.